Characterization of N‐doped carbon quantum dots synthesized by DBD‐based cold atmospheric pressure plasma jet. Issue 12 (17th August 2022) - Mohammadzaheri, Mina; Siahpoush, Vahid; Asgari, Asghar
Abstract: This study develops a new approach for the synthesis of fluorescent N‐doped carbon quantum dots (CQDs), using cold atmospheric pressure plasma jet. Herein, the CQDs were synthesized with two plasma exposure times of 30 and 60 min. The UV‐Vis absorption spectrum confirms the existence of carbonic core and surface functional groups. The Fourier transform infrared spectrum shows that carbonyl groups and amide groups exist on the surface of CQDs. Depending on the plasma exposure time, the mean average sizes of CQDs are 3.63 and 5.45 nm with strong photoluminescence emission. Generally, our results indicated that using different mechanisms for plasma discharge, lead to different physical and chemical properties of produced plasma and consequently of synthesized CQDs. The synthesized N‐doped CQDs exhibited strong fluorescence and higher quantum yield compared to previous reports. Abstract : Carbon quantum dots are a novel type of fluorescent nanomaterial with unique properties, and their synthesis method is an interesting research field. In this study, a new approach for fabrication of carbon quantum dots in one‐step using cold atmospheric pressure plasma jet is suggested, and the influence of different plasma exposure times, which result in control of optical and structural properties of carbon quantum dots, has been investigated in detail.